PENGARUH DISIPLIN KERJA, STRES KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI MASA PANDEMIC COVID-19 - Viorencia Brilianti Sanbowo (Jurnal Ekonomi Manajemen dan Bisnis, 2021)
This study aims to determine the effect of work discipline, work stress, and compensation on employee performance at PT Sinarmas Multifinance Pangkalpinang. The method used is a quantitative method with analytical techniques using multiple linear regression analysis statistics. Based on the results of Multiple Linear Regression analysis with regression, correlation, determination and hypothesis testing, the results show that work discipline has a positive and significant effect on employee performance, work stress has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee performance, and discipline work, work stress, and compensation simultaneously have a significant effect on employee performance.